PENGARUH PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) DAN JIGSAW TERHADAP PRESTASI BELAJAR EKONOMI DITINJAU DARI MOTIVASI BELAJAR SISWA TAHUN AJARAN 2012/2013 - M. Saipul Watoni; Sri Anitah; Hery Sawiji (Jurnal Pendidikan Insan Mandiri, 2014)
This study is aimed at finding out (1)  the effect of STAD and Jigsaw cooperatives learning toward economics learning achievement; (2) the effect of high and low motivations toward economics learning achievement; (3) the interaction between motivation and teaching learning, STAD and Jigsaw types toward economics learning achievement. This study was quantitative research by using experiment method. The population of the study was all students of tenth grade of SMA Negeri 1 Keruak Lombok Timur, in the academic year 2012/2013, the sample was determined by using cluster random sampling and got 2 classes. The teaching learning model in the first experimental class used STAD of XB consisting of 36 students while in the second experimental class used Jigsaw of XF consisting of 35 students.The techniques of collecting data were test for economics achievement, questionnaires for students’ motivation, and documentation. To analyze the hypothesis, the researcher used two-way analysis of variance with a 2x2 factorial design and the significant level was 5%.  The prerequisite test of normality and homogeneity were analyzed by using SPSS 17 software.  From the analysis, it can be concluded that: (1) there is effect of STAD and Jigsaw cooperatives learning toward economics learning achievement; (2) there is effect of high and low motivations toward economics learning achievement; (3) there is no interaction between motivation and teaching learning types STAD and Jigsaw toward economics learning achievement.